Avaliação da eficiência de empresas de construção portuguesas utilizando Data Envelopment Analysis e análise de clusters - Isabel Horta (2008)
The study reported in this paper aims to characterize the performance profile of the PortugueseConstruction Industry. The analysis was based on Key Performance Indicators from a sample comprising58 companies. These are among the largest national construction companies operating in 2007. Themethodological approach involved two different stages: the use of Cluster Analysis to identifyhomogeneous groups of construction companies and the use of Data Envelopment Analysis tocharacterize the performance profile of each cluster. The Data Envelopment Analysis technique wasuseful for assessing the relative efficiency of each company, as well as to identify the strengths,weaknesses and priority areas of improvement for the companies analyzed. Finally, it was determined thetarget level for the indicators of each company corresponding to efficient operation. This quantification oftargets for improvement was supported in a direct comparison with other companies in the sampleconsidered benchmarks.